2018
DOI: 10.1002/hbm.24192
|View full text |Cite
|
Sign up to set email alerts
|

Fronto‐Parietal Subnetworks Flexibility Compensates For Cognitive Decline Due To Mental Fatigue

Abstract: Fronto-parietal subnetworks were revealed to compensate for cognitive decline due to mental fatigue by community structure analysis. Here, we investigate changes in topology of subnetworks of resting-state fMRI networks due to mental fatigue induced by prolonged performance of a cognitively demanding task, and their associations with cognitive decline. As it is well established that brain networks have modular organization, community structure analyses can provide valuable information about mesoscale network o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 76 publications
(105 reference statements)
1
9
0
Order By: Relevance
“…Concurring with previous studies focusing specifically on each functional subsystem [8], [51]- [61], [66], our results indicated that ACC, PCG, and PPC served as the pivotal nodes engaged in the fatigue modulation. Through community structure analyses, the fMRI study [66] reported that fronto-parietal network compensated with cognitive decline due to mental fatigue. That may explain the strong synchronized deactivation of the fronto-parietal regions in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Concurring with previous studies focusing specifically on each functional subsystem [8], [51]- [61], [66], our results indicated that ACC, PCG, and PPC served as the pivotal nodes engaged in the fatigue modulation. Through community structure analyses, the fMRI study [66] reported that fronto-parietal network compensated with cognitive decline due to mental fatigue. That may explain the strong synchronized deactivation of the fronto-parietal regions in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The dynamical analysis is an extension of the EEG measures with a focus on the time sequence of EEG index or functional connectivity networks (Bola and Sabel, 2015;Pagnotta et al, 2020). Previous studies based on perfusion functional magnetic resonance imaging found that the connectivity strength of frontal-parietal network represented by topological characteristics dynamically changes to compensate the cognitive decline during long-term sustained attention task (Taya et al, 2018). The dynamical analysis represents the evolution of neural activity, mostly used is dynamic functional connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Mental fatigue has become a widespread subhealthy condition in nowadays society [ 1 ]. Many researchers are dedicated to the studies of detection methods [ 2 ], neural mechanisms [ 3 ], and mitigation methods [ 4 ] of the mental fatigue, owing to the negative effects of mental fatigue on the human cognitive functions [ 5 ], especially serious in driving fatigue [ 6 ].…”
Section: Introductionmentioning
confidence: 99%